Pengaruh Dana Pihak Ketiga, Efisiensi Operasional dan Tingkat Likuiditas terhadap Kinerja Keuangan dengan Resiko Pembiayaan Sebagai Variabel Moderating pada Perbankan Syariah di Indonesia - Mufidatul Ummah Adhyta; Syaiful Syaiful (Universitas 45 Surabaya, 2024)
This research aims to examine the influence of third party funds, operational efficiency and liquidity levels on the financial performance of Islamic commercial banks. This type of research uses a quantitative approach. The sample selection in this research used the purposive sampling method. The population in this study is all financial report data from quarter 1 to quarter 3 of Sharia Commercial Banks from 2018 to 2022. The sample used in this research is 120 samples from 10 observation data from Islamic commercial banks that have been registered with the Financial Services Authority for the period 2018- 2022. Data were analyzed using the moderated regression analysis test method, classic assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. In this research, return on assets is used to measure the financial performance of Islamic general banking. The dependent variable in this research uses Return On Assets, while the independent variables are data on third party funds, Operating Expenses, Operational Income, and Financing to Deposit Ratio, then for the moderating variable, the Net Performance Financing ratio is used. The results of this research show that the Third Party Funds variable has a negative and insignificant effect on the financial performance of sharia commercial banks, Operational Efficiency (BOPO) has a negative effect on the financial performance of sharia commercial banks, the level of liquidity (FDR) has a negative and insignificant effect on the financial performance of commercial banks Sharia and financing risk variables (NPF) are able to strengthen the interaction relationship between their independent variable.